Masquerading Bundle Branch Block Presenting During Non-ST-Elevation Myocardial Infarction: A Case Report - Umavi Halkewela; Nithurshan Sivanantham; Madushan Rnabhahu; Arulkumar Jegavanthan; Hemal Senanayake (Journal of Tropical Health, 2026)
Background: Masquerading bundle branch block (MBBB) is a rare intraventricular conduction disturbance defined by simultaneous right bundle branch block (RBBB) morphology in the precordial leads and left bundle branch block (LBBB)-like features in the limb leads. It is mainly found in patients with established structural or ischemic heart disease. Because of its morphology, MBBB can mask or mimic ischemic changes, which can lead to diagnostic challenges when a patient presents with acute chest pain.Case Presentation: A 57-year-old man presented with a two-day history of intermittent central chest pain and excessive sweating. The 12-lead ECG showed the characteristic discordant pattern of MBBB. Troponin I (high-sensitivity) was 239 ng/L on arrival and trended down on repeat sampling, confirming myocardial injury. He was treated for acute coronary syndrome, remained stable throughout admission, and was discharged on dual antiplatelet and heart failure therapy with early coronary angiography arranged.Conclusion: This case highlights that MBBB can coexist with acute coronary syndromes while masking their ECG features. Clinicians should recognize this pattern and rely on biomarkers and echocardiography for diagnosis. Close follow-up is essential due to the risk of progression to high-degree heart block.